Exotic Form, Function and Meaning of Bale Adat Kembar of the Great Palace of Kesiman in Denpasar Bali - Anak Agung Gde Putera Semadi (Jurnal Kajian Bali (Journal of Bali Studies), 2023)
The twin traditional buildings (Bale Adat Kembar) at the Great Palace of Kesiman, Denpasar, Bali, is not only a twin building marking the majesty and unique architecture of the palace but also a place to carry out the important ritual of Pitra Yadnya for deceased ancestors. This article analyzes the exotic form, function, and meaning of Bale Adat Twins at the Great Palace of Kesiman, one of the three important palaces which is the heir of the Kingdom of Badung. Using a qualitative approach, the data for this study were collected from interviews with the palace chief, observations, and literature studies. The data were analyzed using a critical approach of Cultural Studies by exploring the deep meaning of the facts, in this case matters related to Bale Adat Kembar. This article concludes that amidst the rapid flow of modernization, the twin traditional building at the Great Palace of Kesiman remains sustainable because it has a ritual function that will always be carried out for Puri's ancestors in accordance with the human life cycle. This article contributes to showing how heritage buildings which are relics of the kingdom still exist with their exoticism in modern times.